Care for the person, protection of health and respect for the will of the patient in Italy: support administration as a tool to jointly promote health and respect for autonomy in incompetent patients - Paola Delbon; Giovanna Ricci; Massimo Gandolfini; Adelaide Conti (SAGE Publishing, 2014)
In Italy, advance health care directives are a subject of considerable debate in both legal theory and practice. This debate focuses in partic- ular not only on the appropriateness of approving ad hoc statutory reg- ulations but also on the extent to which similar advance indications of a person's wishes are applicable under the existing legal system, albeit in the absence of a law regulating them. The authors of this paper con- sider, in particular, guidelines relating to the possible use of the mech- anism of support administration (amministrazione di sostegno) (Law No. 6/2004) as a procedure to be used for the legal recognition of advance health care directives, particularly in the light of the legal pro- vision for the possible designation in advance of a support administra- tor by a beneficiary in anticipation of an eventual situation of incapac- ity. This underlines how the concept of health does not only exist in the abstract, but must be measured in relation to the particular patient in the particular situation and how beneficence and respect for auton- omy are both essential elements in the choices aimed at promoting the health and the wellbeing of its citizens.